Reflective Versus Normative Thinking: Habitus Study on American and Indonesian Graduation Speech - Aris Munandar (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
Graduation and the future are closely related. Graduation is the end of education and the beginning of the future. The ways to perceive these two things might vary due to the influence of cultural backgrounds. This study compares Indonesian and American graduates’ perceptions about graduation and the future by looking at the verbal expressions used in their graduation speeches. Ten speeches by Indonesian graduates and ten speeches by American graduates were selected as data sources. The verbal expression data analysis combines linguistic theory (metaphor) and Bourdieu’s social theory of Cultural Capital and Habitus. The results show that Indonesian and American graduates share nearly the same perceptions about graduation and the future; however, they have different expressions due to different cultural capital and habitus. American graduates express their perceptions reflectively, while Indonesian graduates do it normatively. It is concluded that American graduates’ speeches reflect society’s intellectuality expectations while Indonesian graduates’ speeches reflect expectations for mannership